2023
DOI: 10.1155/2023/2496557
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intrathecal Bupivacaine Plus Dextrose 5% and Fentanyl Compared with Bupivacaine Alone on the Onset and Duration of Analgesia in Patients Undergoing Lower-Limb Orthopedic Surgery

Abstract: Introduction. This study aimed to compare the effect of intrathecal bupivacaine plus dextrose 5% and fentanyl with bupivacaine alone on the onset and duration of analgesia in patients undergoing lower-limb orthopedic surgery. Materials and Methods. A total of 40 patients eligible for lower-limb surgery were divided into two groups by simple randomization: the control group which received only bupivacaine and the intervention group which received bupivacaine plus dextrose 5% and fentanyl. Anesthesia was induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…The co-administration of other adjuvant drugs can reduce the required bupivacaine dose and improve the quality of SA [3]. Several studies have reported improved surgical outcomes by including fentanyl, a lipophilic opioid, in spinal anesthesia [6,[14][15][16][17][18][19][20]. The study assessed the effects of fentanyl in co-administration with bupivacaine during SA, focusing on patient comfort, surgery success, the quality of the spinal block, and side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The co-administration of other adjuvant drugs can reduce the required bupivacaine dose and improve the quality of SA [3]. Several studies have reported improved surgical outcomes by including fentanyl, a lipophilic opioid, in spinal anesthesia [6,[14][15][16][17][18][19][20]. The study assessed the effects of fentanyl in co-administration with bupivacaine during SA, focusing on patient comfort, surgery success, the quality of the spinal block, and side effects.…”
Section: Discussionmentioning
confidence: 99%